1966
DOI: 10.1128/jb.91.5.1744-1749.1966
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Virulence of Candida albicans after Oral Inoculation in the Chick with a Monoflora of Either Escherichia coli or Streptococcus faecalis

Abstract: , N.Y.), AND A. W. PHILLIPS. Growth and virulence of Candida albicans after oral inoculation in the chick with a monoflora of either Escherichia coli or Streptococcus faecalis. J. Bacteriol. 91:1744-1749. 1966.-Bacterial protection against intestinal infection by Candida albicans was investigated in chicks with a monoflora of either Escherichia coli or Streptococcus faecalis. These animals were obtained by orally inoculating germ-free chicks (3 days old) with pure cultures of bacteria. Each bacterial species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…In addition, they recognized that the cecal contents of gnotobiotic chickens were liquid. Such phenomena have already been reported by many investigators [1,3,4,7,10,16,19,20]. Such differences between gnotobiotic and conventional chickens suggest that the intestinal flora may have a great effect on proliferation of E. coli and enterococci as well as on the consistency of the cecal contents.…”
supporting
confidence: 53%
“…In addition, they recognized that the cecal contents of gnotobiotic chickens were liquid. Such phenomena have already been reported by many investigators [1,3,4,7,10,16,19,20]. Such differences between gnotobiotic and conventional chickens suggest that the intestinal flora may have a great effect on proliferation of E. coli and enterococci as well as on the consistency of the cecal contents.…”
supporting
confidence: 53%
“…Congenitally immunodeficient mice were produced by mating homozygous (nulnu, bglbg, or bglbg nulnu) males with heterozygous (nul+, bgl+, and bglbg nul+, respec-1094 CANTORNA AND BALISH bred and housed in flexible film isolators at the University of Wisconsin Gntobiotic Research Laboratory (Madison). The GF or C. albicans-colonized status of each experiment was assessed by methods previously described (5). Confirmation of immune defects in congenitally immunodeficient mice.…”
mentioning
confidence: 99%
“…They concluded that the enteric microbial flora of the conventional chick provides protection against candidiasis. They further demonstrated that Escherichia coli in the intestinal tract of gnotobiotic chicks provides protection against crop infection after oral challenge with C. albicans, whereas Streptococcus faecalis provides no such protection (3). The same workers (21) and Nishikawa et al (20) have also shown that C. albicans can be established in the intestinal tract of germ-free mice and that the fungus will persist for at least 18 months (in the former report) and for 134 days (in the latter study).…”
mentioning
confidence: 99%